2001
DOI: 10.1523/jneurosci.21-04-01257.2001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neuregulin Expression in the Injured Rat Brain and Cultured Astrocytes

Abstract: In this report, we investigated whether reactive astrocytes produce neuregulins (glial growth factor 2/heregulin/acetylcholine receptor-inducing activity or neu differentiation factor) and its putative receptors, ErbB2 and ErbB3 tyrosine kinases, in the injured CNS in vivo. Significant immunoreactivities with antineuregulin, anti-ErbB2, and anti-ErbB3 antibodies were detected on astrocytes at the injured site 4 d after injury to the adult rat cerebral cortex. To elucidate the mechanisms for the upregulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(27 citation statements)
references
References 52 publications
1
25
0
1
Order By: Relevance
“…The upregulation of NRG-1 and erbB receptors in the lesion area after injury may also account for the relatively lower concentrations of NRG-1 required in the in vivo studies compared with the amount required to block proliferation in the VSMC cultures. Similarly, the upregulation of NRG-1 and its erbB receptors has also been reported after ischemia and central nervous system injury [31,32,33,34,35,36]. As seen in the vascular injury model, we showed that administration of exogenous NRG-1 was neuroprotective and prevented inflammatory responses caused by ischemia [32, 37].…”
Section: Discussionsupporting
confidence: 68%
“…The upregulation of NRG-1 and erbB receptors in the lesion area after injury may also account for the relatively lower concentrations of NRG-1 required in the in vivo studies compared with the amount required to block proliferation in the VSMC cultures. Similarly, the upregulation of NRG-1 and its erbB receptors has also been reported after ischemia and central nervous system injury [31,32,33,34,35,36]. As seen in the vascular injury model, we showed that administration of exogenous NRG-1 was neuroprotective and prevented inflammatory responses caused by ischemia [32, 37].…”
Section: Discussionsupporting
confidence: 68%
“…In the adult mouse cortex, erbB4 expression is detected at low levels in some astrocytes (Erlich et al, 2000). Astrocyte expression of erbB3 receptors is only reported during astrogliosis following injury of the rat adult cortex (Tokita et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…56,57 NRG-1 and its receptors are upregulated after traumatic brain injury in rat models. 58,59 NRG-1β exerts a cytoprotective effect against oxidant injury in multiple cell types in the brain, including the microvascular endothelial cell. 60 …”
Section: Nrg In the Central And Peripheral Nervous System: Implicatiomentioning
confidence: 99%